3D Assembly of All‐Inorganic Colloidal Nanocrystals into Gels and Aerogels. Issue 21 (21st April 2016) - Sayevich, Vladimir; Cai, Bin; Benad, Albrecht; Haubold, Danny; Sonntag, Luisa; Gaponik, Nikolai; Lesnyak, Vladimir; Eychmüller, Alexander
Abstract: We report an efficient approach to assemble a variety of electrostatically stabilized all‐inorganic semiconductor nanocrystals (NCs) by their linking with appropriate ions into multibranched gel networks. These all‐inorganic non‐ordered 3D assemblies benefit from strong interparticle coupling, which facilitates charge transport between the NCs with diverse morphologies, compositions, sizes, and functional capping ligands. Moreover, the resulting dry gels (aerogels) are highly porous monolithic structures, which preserve the quantum confinement of their building blocks. The inorganic semiconductor aerogel made of 4.5 nm CdSe colloidal NCs capped with I − ions and bridged with Cd 2+ ions had a large surface area of 146 m 2 g −1 . Abstract : An assembly approach for a variety of electrostatically stabilized all‐inorganic semiconductor nanocrystals is based on their linking with appropriate ions into multibranched gel networks. The resulting aerogels are highly porous monolithic structures, which preserve the quantum confinement of their building blocks.